Pengaruh Perlakuan Shot Peening Terhadap Korosi Retak Tegang Baja Karbon Rendah Pada Lingkungan Korosif - Sujita, S. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2011)
The aim of this study is to investigate the effect of shot peening on stress corrosion cracking of a low carbon steel in ocean water environment. The dimension of specimens were prepared in accordance with the ASTM G39. The hardness testing was carried out using microvickers with 0,25 kgf load in the longitudinal direction. The corrosion cracking test was immersed into artificial sea water for about 7 months. The test shows that the pitting corrosion is dominantly nucleated at the metal film interface. The biggest pitting corrosion was occurred under the static loading of 70 for the specimens unpeened. The presence of pitting corrosion promotes stress corrosion cracking. The cracking has a intergranular branched morphology which is typical for the chloride cracking of low carbon steel